Reversible protein assemblies in the proteostasis network in health and disease - Kohler, Verena; Andréasson, Claes (Frontiers in Molecular Biosciences, 2023)
While proteins populating their native conformations constitute the functional entities of cells, protein aggregates are traditionally associated with cellular dysfunction, stress and disease. During recent years, it has become clear that large aggregate-like protein condensates formed via liquid-liquid phase separation age into more solid aggregate-like particles that harbor misfolded proteins and are decorated by protein quality control factors. The constituent proteins of the condensates/aggregates are disentangled by protein disaggregation systems mainly based on Hsp70 and AAA ATPase Hsp100 chaperones prior to their handover to refolding and degradation systems. Here, we discuss the functional roles that condensate formation/aggregation and disaggregation play in protein quality control to maintain proteostasis and why it matters for understanding health and disease.